CHARACTERIZATION OF THE CLIENTS IN RADIOTHERAPIC TREATMENT IN A SERVICE IN SOUTHERN BRAZIL - Juliana Graciela Vestena Zillmer; Lílian Moura de Lima; Aline Machado Feijó; Eda Schwartz; Claudia das Neves Hisse; Aline da Costa Viegas; Bianca Pozza dos Santos (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928595 Aim: to describe the characteristics of clients with cancer undergoing radiotherapy in a Regional Center of Oncology in Southern Brazil. Method: it is a descriptive quantitative study. Study participants were 147 clients with cancer undergoing radiotherapy from March 2006 to July 2008. Data collection occurred through a semistructured questionnaire. It was used the basic statistics for the analysis using the software Epi Info (6:04). Results: there was predominance of male patients, white color, marital status married/with partner, age over 60 years. The origin was predominantly from the urban area, with income from one to three minimum wages, incomplete primary education. Cancers of the nasopharynx were the most frequent and the treatment prior to radiotherapy was the surgery. Conclusion: the characterization of the clients allows the development of targeted strategies on qualified health care to this population.